A Game of Thrones (A Song of Ice and Fire #1) - George R.R. Martin (Great Britain Harper Voyager, 2003)
Long ago, in a time forgotten, a preternatural event threw the seasons out of balance. In a land where summers can last decades and winters a lifetime, trouble is brewing. The cold is returning, and in the frozen wastes to the north of Winterfell, sinister forces are massing beyond the kingdom's protective Wall. To the south, the king's powers are failing-his most trusted adviser dead under mysterious circumstances and his enemies emerging from the shadows of the throne. At the center of the conflict lie the Starks of Winterfell, a family as harsh and unyielding as the frozen land they were born to. Now Lord Eddard Stark is reluctantly summoned to serve as the king's new Hand, an appointment that threatens to sunder not only his family but the kingdom itself. Sweeping from a harsh land of cold to a summertime kingdom of epicurean plenty, A Game of Thrones tells a tale of lords and ladies, soldiers and sorcerers, assassins and bastards, who come together in a time of grim omens. Here an enigmatic band of warriors bear swords of no human metal; a tribe of fierce wildlings carry men off into madness; a cruel young dragon prince barters his sister to win back his throne; a child is lost in the twilight between life and death; and a determined woman undertakes a treacherous journey to protect all she holds dear. Amid plots and counter-plots, tragedy and betrayal, victory and terror, allies and enemies, the fate of the Starks hangs perilously in the balance, as each side endeavors to win that deadliest of conflicts: the game of thrones. Unparalleled in scope and execution, A Game of Thrones is one of those rare reading experiences that catch you up from the opening pages, won't let you go until the end, and leave you yearning for more.
Keywords: Fantasy; Fiction; Adventure; Adult